Cognitive remediation for depressed inpatients: Results of a pilot randomized controlled trial - Trapp, Wolfgang; Engel, Sinha; Hajak, Goeran; Lautenbacher, Stefan; Gallhofer, Bernd (Australian and New Zealand Journal of Psychiatry, 2015)
Objective: Neurocognitive deficits that persist despite antidepressive treatment and affect social and vocational functioning are well documented in major depressive disorder. Cognitive training approaches have proven successful in ameliorating these deficits in other psychiatric groups, but very few studies have been conducted in unipolar depressive patients by now. In contrast to previous studies solely including outpatients, effects of a cognitive remediation intervention on neurocognitive functioning of depressed inpatients were assessed by the present study. Method: A randomized controlled trial was carried out with 46 depressed inpatients of a psychiatric hospital. Patients were randomly assigned to either a control group that received standard drug and non-drug (cognitive behavioural, occupational, sports, relaxation and music therapy) antidepressive treatment or a remediation group that additionally received 12 sessions of cognitive training for a total of 4 weeks (three sessions per week). An intent to treat analysis and a last observation carried forward method was used for data analyses. Results: Patients of the remediation group demonstrated greater improvements in neurocognitive measures of verbal and nonverbal memory, working memory and executive function (Cohen’s d effect sizes between .52 and .98). Conclusions: These results provide preliminary evidence that cognitive remediation interventions can be successfully applied also in psychiatric inpatients experiencing an acute depressive episod